Development of the Strength and Conditioning Coach Student-Athlete Satisfaction Survey (SCC-SASS) - Megan Lynn Cottet; Michael G. Miller; Thomas A. Cappaert; Mitchel Schwartzman (International Universities Strength and Conditioning Association, 2022)
The purpose of this study was to develop a valid and reliable survey for student-athletes to assess their satisfaction with their strength and conditioning coach (SCC) and the services they provide. This three-round Delphi Method study utilized experts to establish group consensus on survey items. Round one was completed by 28 experts, round two by 24 experts and round three by 22 experts. The Delphi Method resulted in the 32 item Strength and Conditioning Coach Student-Athlete Satisfaction Survey (SCC-SASS). Next, test-retest reliability was established by a sample (n=25) of student-athletes who were asked to complete the SCC-SASS twice, one to six days apart. The mean pre-test score was 126.62, and the post-test score was 126.04. A Two-Way Mixed Intra Class Correlation was run, resulting in an ICC of .956. Finally, Cronbach's alpha was calculated at an alpha value of .98. The results of these tests established the reliability of the SCC-SASS. This study led to the development of a valid and reliable survey to assess student-athlete satisfaction with their SCC and the services they provide. Knowing student-athlete satisfaction is important because student-athletes spend significant time with their SCC and higher athlete satisfaction is commonly associated with increased athletic performance. The development of this tool was vital to aid in assessing SCCs in hopes to further enhance the quality of the profession and the services and quality of care SCCs provide. Keywords: strength coach, college-age, quality improvement tool, group consensus, Delphi Method